2020
DOI: 10.1038/s41401-020-0415-5
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo pulsed dendritic cell vaccination against cancer

Abstract: As the most powerful antigen-presenting cell type, dendritic cells (DCs) can induce potent antigen-specific immune responses in vivo, hence becoming optimal cell population for vaccination purposes. DCs can be derived ex vivo in quantity and manipulated extensively to be endowed with adequate immune-stimulating capacity. After pulsing with cancer antigens in various ways, the matured DCs are administrated back into the patient. DCs home to lymphoid organs to present antigens to and activate specific lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 87 publications
(85 reference statements)
0
40
0
1
Order By: Relevance
“…Generally speaking, T-cell responses induced by mRNA-loaded DC vaccines have been rather weak, which may contribute to the low clinical efficacy. DC differentiation, maturation and antigen loading directly impact DC homing and T cell co-stimulation (reviewed in Gu et al [ 64 ]), and are targets for further improvement of this approach.…”
Section: Mrna-based Cancer Vaccinesmentioning
confidence: 99%
“…Generally speaking, T-cell responses induced by mRNA-loaded DC vaccines have been rather weak, which may contribute to the low clinical efficacy. DC differentiation, maturation and antigen loading directly impact DC homing and T cell co-stimulation (reviewed in Gu et al [ 64 ]), and are targets for further improvement of this approach.…”
Section: Mrna-based Cancer Vaccinesmentioning
confidence: 99%
“…Combinations of SX-682 and anti-PD-1, or anti-PD-L1 antibodies have been tried in clinical trials (Table 2). Snail has been reported to induce regulatory dendritic cells by TSP1 production(51), Flt3 ligand and IL-12, which promote dendritic cell maturation, and peptide-pulsed dendritic cell vaccines, which is a vaccination with specific tumor antigenic peptide-pulsed dendritic cells, could be a good candidate therapy for tumors with EMT properties (130,131). Although immunotherapy cannot solve all the phenomena induced by EMT-TFs, it is worth trying to treat EMT phenotypic tumors.…”
Section: Therapy Targeting Emt-induced Immunosuppressionmentioning
confidence: 99%
“…Actually, mRNA-based therapy was not common before the 2000s due to the instability of mRNA and related excessive inflammation responses. However, technological breakthroughs, including incorporation of modified nucleosides, purification of IVT mRNA, optimization of coding sequences, and development of efficacious delivery material, changed the situation by enabling mRNA optimal form to carry tumor antigens [ 9 , 10 ]. For instance, mRNA sequence can be easily modified to encode any protein, unlike the traditional peptide vaccine that requires genetic analysis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mRNA has no gene integration risk and irrelevant sequence exclusion caused by DNA type, preventing insertional mutagenesis or gene deletion. The self-adjuvant properties of mRNA (e.g., cytokines) increase its in vivo immunogenicity and induce a strong and persistent immune response [ 7 – 10 ]. Preclinical models have demonstrated that the vaccine encoding tumor-specific antigens promotes an anti-tumor immunity and prevents multiple tumors, including melanoma, hepatocellular carcinoma, colorectal cancer, gastrointestinal cancer, and pancreatic adenocarcinoma [ 7 – 13 ].…”
Section: Introductionmentioning
confidence: 99%